ANALISIS SPASIAL DAN FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DEMAM BERDARAH DENGUE (DBD) DI KELURAHAN WATES KECAMATAN WATES KABUPATEN KULON PROGO TAHUN 2013 - , LD. A. Saktiansyah ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: In the last decade of Dengue Hemorrhagic Fever (DHF) become a global health problem, characterized by the increasing cases of dengue in the world. DHF in the Wates District, especially in Wates Village Kulon Progo regency in 2013 based on case report from Wates Local Goverment Clinic January-September period showed a significant increase by 35 cases, and 2 of them died. Objective: To directly the spatial image and factors associated with the incidence of Dengue Hemorrhagic Fever (DHF) in the Wates Village Wates subdistrict Kulon Progo Regency in 2013. Methods: This study is an observational study with cross-sectional design, and using Geographic Information Systems to describe the spatial and the incidence of Dengue Hemorrhagic Fever (DHF) in the Wates Village Wates subdistrict Kulon Progo Regency in 2013. Results: Description of density population in Wates Village is dense category 5011.6792 Jiwa/km2. The existence cases of larvae dengue at home is 78.13% 21.88% positive and negative larvae. The existence of the pupa in dengue cases is 46.88% 53.13% positive and negative pupa pupa. The peoples habits of hanging clothes after used is equal to 84.37%. The frequency of cleaning water reservoirs respondents on average â¤ 1 times in one week of 59.37%. Direction of movement patterns of DHF patients in Wates village leads southeast-Northwest with angle 42Â°. Neighbor nearst Analaysis (NNI) obtained the value Z = -3.11 and p = 0.7 and NNI value = 0.5592. Risk area prediction of DHF in Wates Village are in the dark zone in area Wetan Pasar, Kedungndowo, Dipan, Wonosidi Lor, Durungan, Driyan, and Gadingan. Entomology indicator for the value of Flick Free Rate (FFR) in endemic areas 54% and 51% in whereas sporadic while value of Pupa Index (PI) in endemic areas 96 and 75 in sporadic area. Conclusion: The population density, the presence of larva, pupa existence, hanging clothes habit, frequency of cleaning water reservoirs be a risk factor DHF. There is a clustering of cases of DHF. Wates village region at risk of dengue. Entomology indicator shows FFR values in the low category and PI values in the high category.